Ginkgolide injections in meglumine, combined with edaravone, significantly increases the efficacy in acute ischemic stroke: A meta-analysis - Yan, Mingyuan; Wu, Jing; Wang, Le; Wang, Kaiyue; Li, Lili; Sun, Tianye; Zhang, Han; Zhang, Mi; Zou, Lin; Yang, Songyi; Liu, Jinmin (Frontiers in Pharmacology, 2024)
Objective This study aimed to evaluate the efficacy of combining diterpene ginkgolide meglumine injection (DGMI) with edaravone for the treatment of acute ischemic stroke. This is particularly relevant because Western drugs, excluding intravenous thrombolysis, have shown limited success. Methods A comprehensive search was conducted using multiple databases, including PubMed, Cochrane Library, Web of Science, China National Knowledge Infrastructure WanFang, VIP, and Chinese Biomedical Database (CBM) until June 2023. The data were analyzed using fixed-effects and random-effects models in Review Manager. The mean difference with 95% confidence interval was calculated for each outcome. Results Eighteen studies involving 1,636 participants were included in the analysis. The DGMI group showed significant reductions in the National Institutes of Health Stroke Scale (NIHSS) score, modified Rankin Scale (mRS) score, and C-reactive protein (CRP) level, compared to the control group. Furthermore, the DGMI group showed a significant improvement in superoxide dismutase (SOD) levels and a reduction in malondialdehyde (MDA) levels. The combination of DGMI and edaravone was more effective in reducing neuron-specific enolase (NSE) levels following brain tissue injury than edaravone alone. Additionally, DGMI complemented edaravone in reducing rheological parameters associated with ischemic stroke, including hematocrit, plasma viscosity, platelet adhesion rate, and erythrocyte deformation index. Conclusion The combination of DGMI and edaravone significantly improved the therapeutic efficacy in patients with acute ischemic stroke. However, more extensive and high-quality clinical trials are required to validate these underlying mechanisms. Systematic Review Registration: https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=260215, identifier: PROSPERO (CRD42021260215)